The Meaning of agalma, eidôlon, and eikôn in Ancient Greek Texts: A Quantitative Approach Using Computer-Driven Methods and Tools - Jurczyk, Thomas (Entangled Religions, 2023)
This article analyzes the use and meaning of central Greek terms related to images in ancient Greek texts collected in the Diorisis Ancient Greek Corpus (Alessandro Vatri and McGillivray 2018). In contrast to the existing literature on the (religious) status of images in Greco-Roman Antiquity, Judaism, and Christianity, this article applies a mixed-methods approach, combining quantitative and computer-driven examinations with a qualitative analysis of selected sentences. The examination of the use and meaning of agalma, eidôlon, and eikôn considers various religious contexts (Jewish and Christian as well as Greco-Roman polytheistic), thereby embedding this article in the larger framework of comparative religious research on synchronic inter-religious contact.